Inhibition of the Nef regulatory protein of HIV-1 by a single-domain antibody - Bouchet, Jérôme; Basmaciogullari, Stéphane E.; Chrobak, Pavel; Stolp-Rastätter, Bettina; Bouchard, Nathalie; Fackler, Oliver Till; Chames, Patrick; Jolicoeur, Paul; Benichou, Serge; Baty, Daniel (Blood, 2011)
The Nef protein of HIV-1 is important for AIDS pathogenesis, but it is not targeted by current antiviral strategies. Here, we describe a single-domain antibody (sdAb) that binds to HIV-1 Nef with a high affinity (Kd = 2 × 10−9M) and inhibited critical biologic activities of Nef both in vitro and in vivo. First, it interfered with the CD4 down-regulation activity of a broad panel of nef alleles through inhibition of the Nef effects on CD4 internalization from the cell surface. Second, it was able to interfere with the association of Nef with the cellular p21-activated kinase 2 as well as with the resulting inhibitory effect of Nef on actin remodeling. Third, it counteracted the Nef-dependent enhancement of virion infectivity and inhibited the positive effect of Nef on virus replication in peripheral blood mononuclear cells. Fourth, anti-Nef sdAb rescued Nef-mediated thymic CD4+ T-cell maturation defects and peripheral CD4+ T-cell activation in the CD4C/HIV-1Nef transgenic mouse model. Because all these Nef functions have been implicated in Nef effects on pathogenesis, this anti-Nef sdAb may represent an efficient tool to elucidate the molecular functions of Nef in the virus life cycle and could now help to develop new strategies for the control of AIDS.